Penerapan Ergonomi Pada Redesign Prasarana Kursi Penumpang Bus Kampus - Sulung Rahmawan Wira Ghani; Sumarsono (Discovery, 2024)
This research aims to redesign the campus bus passenger seats to be ergonomic and comfortable, considering the feasibility of health risk while riding. Campus bus transportation often causes musculoskeletal complaints among passengers due to outdated infrastructure. This research combines the REBA (Rapid Entire Body Assessment) method to assess posture risk and the Nordic Body Map (NBM) to identify passenger complaints. The REBA analysis results show a risk of musculoskeletal injury in passengers' sitting posture when using the old seats. NBM identifies the most frequently complained body areas, such as the back, neck, and shoulders. The seat redesign was carried out by considering the results of REBA and NBM analyses, resulting in seats that support healthier sitting postures and reduce complaints. This research demonstrates that ergonomic seat design can improve the feasibility of health risk while riding and the quality of the campus bus passenger experience